(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The ‘Vaso de los Letreros’ of Liria (Valencia, Spain) is a large earthen jar, decorated with a picture of an heroic episode in wich one rider is pursue by others ones. The jar is full of iberic inscriptions. The greatest is in the top of the scene. We believe that it is possibly a fragment of one literary text related with the picture. After various attempts we present an essay of identification of possibly fourth verses.